Clinical observations in TVT affected dogs treated with Vincristine sulphate - JAIN, ANITA; TIWARl, R P; TIWARI, S K; AWASTHl, M K (The Indian Journal of Animal Reproduction, 2023)
Six healthy and six TVT affected dogs were treated with Vmcristine sulphate @0.025 mg/ kg body wt,1/V at weekly interval for 5 weeks while 6 TVT affected dogs were surgically operated and after one week theywere treated with vincristine sulphate at same dose rate and interval for three weeks at weekly interval. Five(83. 33%) animals recovered completely between two to five weeks period while one dog that was having extragenitalmetastasis did not recover in vincristine sulphate treated group. All the dogs (6/6) recovered completely withoutrecurrence with surgical excision of tumour followed by vincristine sulphate administration. Side effects of vincristinesulphate injection included vomition, constipation, anorexia and alopecia. There 'Yas significant rise of bodytemperature (P
Keywords: Canine Transmissible Venereal Tumour (CTVT); vincristine sulphate